INTEGRATION OKRS OF INSTRUCTIONAL SUPERVISION IN THE DIGITAL ERA FOR SUCCESS OF TEACHERS’ LEARNING MANAGEMENT - Kruekamai, Wachira; Kodsiri, Chawalit; Payakkul, Daranee (Journal of Buddhist Anthropology, 2021)
This article aims to discuss instructional supervision in the digital era with the concepts of Objective and Key Results (OKRs) integrated and applied to promote the success of teachers’ learning management. This is because the role of digital society plays in many areas of technological adoption including instructional supervision in which reflects the quality of teachers’ learning management and academic staff performance. The crucial aspect of technological change, besides teachers’ technology adoption, lies on the objectives of teachers to be explicitly stated and be possibly put into practice as well as the adaptations of teachers to coping with global changes, directly leading to Key Results to learners. The application of the OKRs concepts aligns with the processes of instructional supervision empowering teachers for their effective learning management. The methods involve setting goals, practicing, and monitoring the instructional processes in which supervisors need to supervise, help, advise, and continuously monitor. Therefore, the discussions and exemplifications of OKRs in this article address the linkage of the application of instructional supervision. Readers know its guidelines or methods of how to integrate the instructional supervision in the digital era with the concepts of OKRs that both teachers and their colleagues have put into practice for earning their achievements. Indeed, it is the cumulative development of ideas from making use the knowledge created by the networks of professional learning community where ICT is applied to creating cooperative learning from reflective thinking.